Gobble: A Decision-Based Game Proposal to Dietary Education - Oliveira, Lucas Barcellos; Santos, Rafael Batista dos; Parreiras, Marcus; Xexéo, Geraldo Bonorino (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This article proposes a game-based approach to nutrition teaching, with the aim of making the topic more engaging and intuitive. This game focuses on the presentation of random scenarios, presented in the form of cards, for which the players must make a decision and observe its impact on key nutrition indicators. This game-based approach has the potential to promote positive eating habits and contribute to improved public health outcomes.